Gender and Development (GAD): Keterpilihan Perempuan dalam Pilkada Serentak 2015, 2017 dan 2018 di Provinsi Jawa Timur - Susi Dian Rahayu; Chairunnisa Chairunnisa (Badan Pengawas Pemilihan Umum, 2018)
The changes of the local government management system after the New Order regime from centralistic to decentralized provide significant changes to the region in Indonesia. Since that time, the region can determine its own affairs and needs, including the regional head. Direct regional head election (local election) is a product of decentralization. Through direct elections, the people have the right to determine their regional heads. In addition, direct elections also opened up opportunities for female candidates to compete in the elections, not a few of them won the contest. In the aftermath of the 2018 Local election, East Java Province has ten female regional heads spread in 38 regency/city, and is the only Province in Indonesia which is currently headed by a female governor. This paper analyzes the electability of women in the localelections in 2015, 2017 and 2018 in East Java as an implementation of the Gender and Development (GAD) concept. In addition, the analysis used in assessing women’s electability in the local election in East Java Province uses four indicators, namely the basis of electability, the pattern of recruitment, regeneration of political party and also bonding with the community (grassroots).